Chemical compositions of mineral precipitates from the Polaris hydrothermal field, Gakkel Ridge - Albers, Elmar; Diehl, Alexander; Fitzsimmons, Jessica N; Jensen, Laramie T; Klein, Frieder; McDermott, Jill M; Purser, Autun; Seewald, Jeffrey S; Walter, Maren; Wegener, Gunter; Bach, Wolfgang; Boetius, Antje; et al. (PANGAEA, 2025)
This dataset contains mineral chemical compositions of hydrothermal precipitates, including those of talc and chlorite, collected at the Polaris hydrothermal field on the ultraslow-spreading Gakkel Ridge, Arctic Ocean. The samples were retrieved from 3,156 m depth by gravity coring at station PS101/180, R/V Polarstern Expedition PS101; besides the recovery of these precipitates in the core catcher the gravity core was empty. Major elemental compositions (in wt.%) were obtained via energy dispersive X-ray spectrometry. Details on the analytical procedure and uncertainties can be found in Albers et al. (submitted).
Keywords: basalt; Gakkel ridge; Geochemistry; hydrothermal system